Ice action on wharf at Strathcona Sound - Frederking, R. M. W.; Sinha, N. K. (1977)
A program to determine ice forces and behaviour was carried out on a wharf at Strathcona Sound on Baffin Island during the winter 1975-76. Observations at the site revealed that tidal action resulted in the formation of an increasingly wide and thick zone of ice between the wharf and the natural ice cover. A qualitative model for developing ice pressures is postulated based on this behaviour. The gauges selected to measure horizontal ice pressures proved to be unsatisfactory so no direct measurements were obtained. It was possible however, from secondary calculations, to establish that horizontal ice pressures of the order of 500 kPa were developed. Un programme mis au point pour déterminer le comportement et les effets de la glace a été mis à l'essai sur un quai à la baie de Strathcona dans l'île de Baffin au cours de l'hiver de 1975-1976. Les études sur place ont révélé que la marée entraîne la formation d'une couche de glace de plus en plus étendue et épaisse entre le quai et la couche de glace naturelle. On tente d'établir un modèle qualitatif pour le calcul des pressions dues à la glace en se fondant sur ces résultats. Les transducteurs choisis pour mesurer les pressions horizontales dues à la glace n'ont pas donné un rendement suffisant et aucune mesure directe n'a pu être prise. D'après les calculs secondaires, cependant, on a pu déterminer que les pressions horizontales dues à la glace atteignaient 500 kPa. Peer reviewed: No NRC publication: Yes